The romance and the reality between pre-service teachers' beliefs about the potential benefits of a short-term study abroad programme and their practices. Issue 7 (2nd October 2016) - Tam, Angela Choi Fung
Abstract: This qualitative study aimed to explore Hong Kong pre-service teachers' beliefs about the potential benefits of a short-term study abroad programme and their practices. Pre- and post-programme semi-structured interviews and reflective journals were employed to collect data. The findings suggest that the transformation of beliefs into practices plays a critical role in the actualization of possible learning outcomes, such as increasing the use of the target language, fostering pedagogical development, broadening cultural understanding and nurturing personal growth. The programme per se, however, does not guarantee target language enhancement in a short time. Implications for programme coordinators and future research are discussed.